2018
DOI: 10.1002/fsn3.857
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to organic and inorganic sources of copper: Differential response in intestinal cell lines

Abstract: ScopeCopper supplementation in nutrition has evolved from using inorganic mineral salts to organically chelated minerals but with limited knowledge of the impact at the cellular level.MethodsHere, the impact of inorganic and organic nutrient forms (glycinate, organic acid, and proteinate) of copper on the cellular level is investigated on intestinal cell lines, HT29 and Caco‐2, after a 2‐hr acute exposure to copper compounds and following a 10‐hr recovery.ResultsFollowing the 10‐hr recovery, increases were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gut microbiota has been widely recognized to influence the digestion and absorption of nutrients by the host, and it plays an important role in maintaining host immune response and healthy growth (Keenan et al, ; Valdes, Walter, Segal, & Spector, ). The gut microbiota is easily influenced by the changes in the microbial milieu and health status of the host and closely related to the growth stage and daily dietary intake of the host.…”
Section: Long‐term Supplementation Of High Copper Diet and Intestinalmentioning
confidence: 99%
“…Gut microbiota has been widely recognized to influence the digestion and absorption of nutrients by the host, and it plays an important role in maintaining host immune response and healthy growth (Keenan et al, ; Valdes, Walter, Segal, & Spector, ). The gut microbiota is easily influenced by the changes in the microbial milieu and health status of the host and closely related to the growth stage and daily dietary intake of the host.…”
Section: Long‐term Supplementation Of High Copper Diet and Intestinalmentioning
confidence: 99%
“…Joanne Keenan et al compared organic and inorganic copper exposure to HT29 and Caco-2 cells. Their findings showed that PepT1, ZnT1, and CTR1 were increased, particularly for CuSO 4 and copper proteinate in Caco-2 cells [17].…”
Section: Introductionmentioning
confidence: 95%
“…The effect of intestinal microbiota on nutrient uptake and maintaining healthy growth is broadly known ( Keenan et al., 2018 ). The gut microbiota changes that occur are related to animal production phase and feed composition.…”
Section: Introductionmentioning
confidence: 99%